Synthesis of compounds related to the anti-migraine drug eletriptan hydrobromide - Madasu, Suri Babu; Vekariya, Nagaji Ambabhai; Kiran, M. N. V. D. Hari; Gupta, Badarinadh; Islam, Aminul; Douglas, Paul S.; Babu, Korupolu Raghu (Beilstein Journal of Organic Chemistry, 2012)
Eletriptan hydrobromide (1) is a selective serotonin (5-HT1) agonist, used for the acute treatment of the headache phase of migraine attacks. During the manufacture of eletriptan hydrobromide the formation of various impurities were observed and identified by LC–MS. To control the formation of these impurities during the preparation of active pharmaceutical ingredients, the structure of the impurities must be known. Major impurities of the eletriptan hydrobromide synthesis were prepared and characterized by using various spectroscopic techniques, i.e., mass spectroscopy, FTIR , 1H NMR, 13C NMR/DEPT, and further confirmed by co-injection in HPLC. The present study will be of great help in the synthesis of highly pure eletriptan hydrobromide related compounds.
Keywords: characterization; control; eletriptan; origin; related substances